Method for preparing microporous material from ashore hazardous waste and incineration products and application
By using oil-containing sludge, rock debris sludge and incineration products generated during offshore oil mining as raw materials, microporous materials are prepared, which solves the problems of high cost of solid waste treatment and difficulty in resource utilization, and achieves efficient building materials and sewage treatment effect.
Patent Information
- Application Number
- CN202411563591.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art is difficult to effectively treat oil-containing sludge and rock-cut sludge cakes generated during offshore oil extraction, as well as slag and fly ash in incineration products, resulting in high cost of solid waste treatment, high energy consumption, and failure to achieve harmlessness. and resource utilization.
A method is used to prepare microporous materials for oil-containing sludge, rock chip mud cake, slag and fly ash as raw materials, and after screening, drying, ball milling, blending, rubbing, drying, preheating and high-temperature roasting, microporous materials are prepared for construction. In the fields of substrates, thermal insulation, green plants and sewage treatment.
It realizes the safe treatment and resource utilization of hazardous solid waste, reduces production costs, improves the lightweight, high-strength, thermal insulation and insulation properties of building materials, and effectively removes organic matter and heavy metals in sewage treatment, reducing environmental pollution .
Smart Images

Figure CN119241114A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of petrochemical hazardous waste treatment, and in particular to a method and application of preparing microporous materials from landed hazardous waste and incineration products. Background Art
[0002] As the depth of oilfield exploitation continues to extend, the types and components of drilling fluids have become more complex and diverse, and the amount of mud cuttings has also increased significantly. In particular, the large-scale use of chemical additives has led to mud cuttings containing a large amount of salts, polymers, clays and other pollutants. It is understood that the production of cuttings mud in the Bohai Sea region is 8,000t / a-10,000t / a. Therefore, how to deal with drilling cuttings has become a primary issue at present.
[0003] In addition, during the process of offshore oil exploration, mining, refining, processing, storage and transportation, oily sludge with high oil content, complex composition, good colloid stability, strong internal adhesion of colloid, toxicity and flammability is also produced. According to statistics, the output of oily sludge in the Bohai Sea area is 6000t-8000t. With the in-depth exploitation of oil, the output of oily sludge will continue to increase. If it is not handled, it will pose a threat to the ecological environment and human health.
[0004] At the same time, with the increase in offshore oil production, the onshore wastewater reception and treatment load will inevitably increase. Through the determination and analysis of the pollutant composition and properties in the wastewater, it is found that the wastewater quality is more complex, with a large content of heavy metals and a high concentration of organic pollutants. The pollutants mainly exist in the wastewater in three states: suspended, colloidal and dissolved. Due to the presence of colloids in the wastewater, the wastewater presents a relatively stable state, but the presence of colloids is directly related to the stable operation of the entire wastewater treatment process and the quality of the treatment effect. Therefore, the colloids need to be further treated to meet the requirements. According to the treatment process, the wastewater treatment process can be divided into the following stages: (1) catalytic oxidation stage; (2) flotation sedimentation stage; (3) filter press dehydration stage. According to statistics, the amount of filter press dehydration products generated by wastewater treatment each year is 1000t-1500t. If they are not treated and randomly piled up, they will not only occupy a large amount of land, but also pollute the environment. Therefore, achieving compliant treatment and disposal of solid waste from offshore oil landings plays a vital role in oilfield production.
[0005] There are many methods for treating the above solid waste, including solvent extraction, hot washing, pyrolysis, incineration, electrochemical treatment technology, etc. Although these methods can effectively reduce the concentration of pollutants in solid hazardous waste and meet the requirements for pollutant discharge, most pollutants will change their phase after being treated by the above methods, resulting in entering the environment in other states, which cannot achieve the goals of harmless treatment and resource utilization. In addition, the treatment cost is high, the energy consumption is large, and it cannot meet the needs of circular economic development. In addition, there are few reports on the research of preparing microporous materials using hazardous solid waste from the petrochemical industry as raw materials. Summary of the invention
[0006] In view of this, the present invention aims to propose a method and application of preparing microporous materials from landed hazardous waste and incineration products, wherein the microporous materials are prepared using oily sludge, rock chip mud cakes produced in the process of offshore oil extraction, and slag and fly ash produced in the process of hazardous waste incineration as raw materials, and the obtained microporous materials have better performance in terms of building substrates, thermal insulation, sound insulation, green plants, and removal of organic matter in sewage (waste) water, which can not only solve the problem of difficult treatment and disposal of hazardous solid waste, but also reduce production costs, while realizing the resource utilization of solid waste, providing direction for the sustainable development of enterprises.
[0007] To achieve the above object, the technical solution of the present invention is implemented as follows: a method for preparing microporous materials from landed hazardous waste and incineration products, comprising the following steps:
[0008] Step S1, taking a certain amount of four raw materials, namely, oily sludge, rock chip cake, slag, and fly ash, screening out the raw materials with large particle sizes for crushing, and then storing the four raw materials separately;
[0009] Step S2, using an oven to dry the four raw materials respectively;
[0010] Step S3, using a ball mill to process the oily sludge, rock chip cake and slag respectively;
[0011] Step S4, the treated sample is mixed with fly ash according to the mass percentage, and the mixing time and particle size need to be controlled;
[0012] Step S5, adding water to the mixed sample, and then kneading it into raw material balls;
[0013] Step S6, placing the obtained raw material balls in an oven for drying;
[0014] Step S7, the dried raw balls are sieved through a standard sieve to obtain semi-finished raw balls;
[0015] Step S8, preheating the raw balls obtained after screening;
[0016] Step S9, calcining the spherical material after the preheat treatment at high temperature;
[0017] Step S10, after the furnace temperature is lowered, the spherical material is taken out and sieved to obtain the final microporous material required.
[0018] Furthermore, the hazardous waste brought ashore is oily sludge and rock debris cake, the incineration products are slag and fly ash produced by the operation of the incinerator, and the raw materials used to prepare the microporous material come from one or more of them.
[0019] Furthermore, in step S1, the raw materials with large particle sizes are screened out through a sieve with a mesh particle size of 20 mm; the raw materials are processed by a crusher so that the particle size of the raw material blocks is ≤25 mm;
[0020] In step S2, when the four raw materials are dried separately, the drying temperature is 60°C-110°C, and the moisture content of the four raw materials after drying is ≤2%.
[0021] Furthermore, in step S3, the raw material is pre-treated with a ball mill for 5 min to 30 min to obtain a powder sample, and the particle size of the powder sample is ≤320 mesh.
[0022] Furthermore, in step S4, after the four powdery samples are blended according to mass percentage, the mass percentage of the oily sludge is 2%-35%, the mass percentage of the rock chip cake is 15%-75%, the mass percentage of the slag is 3%-20%, and the mass percentage of the fly ash is 5%-50%.
[0023] Further, step S5 includes, weighing the four raw materials after mixing, adding water according to the weight, controlling the amount of water added each time according to 3%-15% of the total weight of the mixed sample, and then kneading the mixed raw materials into raw material balls.
[0024] Furthermore, in step S6, the drying temperature is 80°C-100°C, and the drying time is 8h-20h; in step S7, the aperture of the standard sieve used for screening the raw balls is 0.4mm-1.0mm.
[0025] Furthermore, in step S8, the preheating temperature is set to 200°C-500°C, and the holding time is 5min-60min during the preheating treatment; in step S9, the control temperature of the high-temperature roasting is 1000°C-1260°C, and the control time is 30min-120min.
[0026] The invention also provides a microporous material prepared by the above method.
[0027] The present invention also provides an application of the microporous material in the field of building substrates.
[0028] Compared with the prior art, the method and application of preparing microporous materials from landed hazardous waste and incineration products described in the present invention has the following advantages:
[0029] (1) The present invention uses oily sludge, rock debris cakes produced in the process of offshore oil extraction, and slag and fly ash produced in the process of hazardous waste incineration as raw materials to prepare microporous materials. The obtained microporous materials have excellent performance in building substrates, thermal insulation, sound insulation, green plants, and removal of organic matter in sewage (wastewater). The specific application areas are as follows:
[0030] ① Microporous materials are lightweight (more than 80% lighter than concrete), high strength, and low density (generally around 400kg / m 3 With good heat insulation performance, it can be widely used in various construction projects in the construction field, such as various types of prefabricated components and cast-in-place concrete projects in industrial and civil buildings;
[0031] ② Microporous materials have good thermal insulation properties due to their light weight and porous structure. Using them on the outside of buildings can not only effectively reduce energy consumption and improve the energy efficiency of buildings, but also be suitable for exterior decoration or structural parts of buildings that need to reduce noise pollution. Microporous materials can also be used for pipe insulation, furnace insulation, etc.
[0032] ③ Microporous materials are very suitable for landscaping and indoor greening due to their porous, light and high surface strength characteristics. They can not only meet the water needs of plants, but also ensure good air permeability, and are especially suitable for the cultivation of indoor ornamental plants;
[0033] ④ Microporous materials can be used as filter media in biological filters to provide a surface for microorganisms to attach and grow. These microorganisms can decompose organic matter in water to purify water quality; in the treatment of industrial wastewater and domestic sewage, microporous materials can improve treatment efficiency, reduce sludge production, and due to their acid and alkali resistance and flushing resistance, they can reduce the frequency of filter media replacement; the porous structure and high specific surface area of microporous materials enable them to effectively adsorb heavy metal ions in water, such as lead, cadmium, chromium, etc., reducing the impact of these harmful substances on the environment and human health. More importantly, in the oil-water separation process of the petrochemical industry, especially when treating oily wastewater, microporous materials can be used as filter media to help separate oil droplets and water, which has a positive effect on reducing the oil load of subsequent processes and can also become a way of resource utilization.
[0034] (2) It can not only solve the problem of difficult treatment and disposal of hazardous solid waste, but also reduce production costs, while realizing the resource utilization of solid waste and providing direction for the sustainable development of enterprises;
[0035] (3) The preparation and acquisition of microporous materials can not only utilize various solid wastes in production and life, such as oily sludge, rock mud cake, urban garbage, coal gangue, various tailings, etc. These wastes can be transformed into useful building materials through appropriate ingredients and process treatment, thus achieving the goal of efficient reuse of resources;
[0036] (4) Through resource utilization, the pollution of waste to the environment is reduced. For example, if solid waste is directly landfilled without treatment, it will occupy a large amount of land and cause environmental problems. After conversion into microporous materials, it not only solves the problem of solid waste treatment, but also reduces the impact on the environment;
[0037] (5) The present invention utilizes materials that can promote the formation of fine honeycomb micropores in the raw material at high temperature, which can not only destroy the chemical composition of the original material to achieve the requirement of reducing the concentration of pollutants. At the same time, because most of the heavy metals, precious metals and other impurities form new phases and solidify in them under the action of high temperature, their long-term existence in the environment not only avoids harm to the ecological environment, but more importantly, it can also reduce production costs, save energy and reduce carbon emissions, and provide a way to promote the sustainable development of enterprises, solving a series of problems such as large output of hazardous waste and incineration products on land, complex components, difficult treatment, and high costs;
[0038] (6) The product prepared by the present invention has a fine honeycomb microporous structure, and has excellent impermeability, low water absorption, heat resistance, high porosity, high compressive strength, strong stability in containing pollutants, low metal leaching, and no pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0040] Figure 1 A flow chart for modulation of microporous materials;
[0041] Figure 2 This is the SEM image of the microporous material after modulation;
[0042] Figure 3 Thermogravimetric diagram of microporous insulation during the modulation process;
[0043] Figure 4 This is the X-ray diffraction analysis diagram of microporous materials. DETAILED DESCRIPTION
[0044] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0045] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.
[0046] like Figure 1 As shown, the present invention is a method for preparing microporous materials from landed hazardous waste and incineration products, wherein the landed hazardous waste is oily sludge and rock debris mud cake, and the incineration products are slag and fly ash produced by the operation of the incinerator, and the raw materials used for preparing the microporous materials are one or more of them. The method comprises the following steps:
[0047] Step S1, taking a certain amount of four raw materials, namely, oily sludge, rock chip cake, slag and fly ash, screening out the raw materials with large particle size for crushing, and then storing the four raw materials separately; specifically, screening out the raw materials with large particle size through a sieve with a mesh particle size of 20 mm; and processing the raw materials with a crusher so that the particle size of the raw material blocks is ≤25 mm.
[0048] Step S2, using an oven to dry the four raw materials separately; wherein, when the four raw materials are dried separately, the drying temperature is 60° C.-110° C., and the moisture content of the four raw materials after drying is controlled to be ≤2%.
[0049] Step S3, using a ball mill to process the oily sludge, rock chip cake and slag respectively; the processing time for pre-treating the raw materials using the ball mill is 5min-30min to obtain a powder sample, and the particle size of the powder sample is ≤320 mesh.
[0050] Step S4, the treated sample is mixed with fly ash according to the mass percentage, wherein the proportion of oily sludge is 2%-35%, the proportion of rock chip cake is 15%-75%, the proportion of slag is 3%-20%, and the proportion of fly ash is 5%-50%. The mixing time is controlled at 1-60min, and the particle size can be controlled according to the grinder to reach 150-300 mesh;
[0051] Step S5, adding water to the blended sample, and then kneading it into raw balls; specifically, the four raw materials are mixed and weighed, and then an appropriate amount of water is added according to the weight, and the amount of water added each time is controlled according to the total weight of the mixed sample weighed each time, and the control ratio is 3%-15%. Specifically, the amount of water added each time is controlled according to 3%-15% of the total weight of the mixed sample, and then the mixed raw materials are kneaded into raw balls.
[0052] Step S6, placing the obtained raw material balls in an oven for drying; wherein the drying temperature is 80°C-100°C, and the drying time is 8h-20h.
[0053] Step S7, the dried raw balls are sieved through a standard sieve to obtain semi-finished raw balls; wherein the aperture of the standard sieve used for sieving the raw balls is 0.4mm-1.0mm.
[0054] Step S8, preheating the raw balls obtained after screening; wherein, during the preheating treatment, the preheating temperature is set to 200°C-500°C, and the insulation time is 5min-60min.
[0055] Step S9, high-temperature roasting the spherical material after preheating treatment; wherein the control temperature of high-temperature roasting is 1000° C.-1260° C., and the control time is 30 min-120 min.
[0056] Step S10, after the furnace temperature is lowered, the spherical material is taken out and sieved to obtain the final microporous material required.
[0057] The invention also provides a microporous material prepared by the above method.
[0058] The present invention also provides an application of the microporous material in the field of building substrates.
[0059] In addition to being applied to the field of building substrates, the present invention can also be applied to building fields such as thermal insulation, heat insulation, and sound insulation, as well as to plant cultivation and wastewater treatment such as green plants and removal of organic matter in sewage (waste) water. The specific application areas are as follows:
[0060] ① Microporous materials are lightweight (more than 80% lighter than concrete), high strength, and low density (generally around 400kg / m 3 With good heat insulation performance, it can be widely used in various construction projects in the construction field, such as various types of prefabricated components and cast-in-place concrete projects in industrial and civil buildings;
[0061] ② Microporous materials have good thermal insulation properties due to their light weight and porous structure. Using them on the outside of buildings can not only effectively reduce energy consumption and improve the energy efficiency of buildings, but are also suitable for exterior decoration or structural parts of buildings that need to reduce noise pollution; microporous materials can also be used for pipe insulation, furnace insulation, etc.
[0062] ③ Microporous materials are very suitable for landscaping and indoor greening due to their porous, light and high surface strength characteristics. They can not only meet the water needs of plants, but also ensure good air permeability, and are especially suitable for the cultivation of indoor ornamental plants;
[0063] ④ Microporous materials can be used as filter media in biological filters to provide a surface for microorganisms to attach and grow. These microorganisms can decompose organic matter in water to achieve the purpose of purifying water quality;
[0064] ⑤ In the treatment of industrial wastewater and domestic sewage, microporous materials can improve treatment efficiency, reduce sludge production, and due to their acid and alkali resistance and flushing resistance, they can reduce the frequency of filter material replacement; the porous structure and high specific surface area of microporous materials enable them to effectively adsorb heavy metal ions in water, such as lead, cadmium, chromium, etc., reducing the impact of these harmful substances on the environment and human health. More importantly, in the oil-water separation process of the petrochemical industry, especially when treating oily wastewater, microporous materials can be used as filter media to help separate oil droplets and water, which has a positive effect on reducing the oil load of subsequent processes and can also become a way of resource utilization.
[0065] The three raw material components of oily sludge, rock chip cake and fly ash contain a large amount of SiO2, Al2O3 and Fe2O3; slag and fly ash contain a large amount of CaO and MgO; in addition, the four raw materials also contain a small amount of K2O, Na2O, CaO, MgO, TiO2 and other components. According to the requirements of modulating microporous materials, SiO2, Al2O3 and Fe2O3 are of great significance in the process of preparing microporous materials with certain mechanical strength. The above three components are their skeleton structures, while MgO, CaO, Na2O and K2O play a role in helping melting and reducing the sintering point in the process of modulating microporous materials, but the addition amount should not be too much, otherwise it will lead to an increase in the liquid phase in the material, which is not conducive to resource utilization.
[0066] The present invention needs to pre-treat the four raw materials before modulating the microporous material, the purpose of which is to increase the contact area of the four materials, promote the occurrence of melting reaction of the fusible component in the subsequent modulation process, and promote the formation of a rich internal pore structure; in addition, by drying, it can avoid the wet material ball from breaking due to excessive temperature changes during the modulation process. In the preheating stage, the raw material ball will lose weight during the heating and sintering process. At the beginning, the surface of the raw material ball will undergo an exothermic reaction due to the evaporation of capillary bound water and adsorbed water and the decomposition of internal organic matter. In addition, as the temperature rises, some relatively stable organic matter begins to volatilize and decompose, promoting the generation of internal pores.
[0067] The raw material ball contains a large amount of quartz, a small amount of microcline, calcite, halite, barite and gypsum, among which the quartz component is SiO2, the microcline component is K (AlSi2O8), the calcite component is CaCO3, the halite components include NaCl, KCl, MgCl2, CaCl2, MgSO4, CaSO4, etc., the barite component is BaSO4, and the gypsum component is CaSO4·2H2O. The microporous material obtained after modulation contains a large amount of quartz, albite and pyroxene, among which the main component of albite is Na2O·Al2O3·6SiO2, and the main component of pyroxene is XY(Si,Al)2O6, where X represents Ca, Na, Mg, Fe2+ , Zn, Ba and Mn, Y represents smaller ions such as Cl, Al, Fe 3+ It contains a small amount of microcline, calcium feldspar, anhydrite and hematite, among which the main component of calcium feldspar is CaAl2Si2O8, the main component of anhydrite is CaSO4·5H2O, and the main component of hematite is Fe2O3. Na2O, Al2O3 and SiO2 contained in the raw material ball will melt under high temperature conditions, prompting rearrangement and combination to form the structure of sodium feldspar crystals. Microcline exists before and after modulation. Due to the presence of Al2O3 and insufficient iron, it not only has a low melting temperature but also a wide melting range. It can be used as a material component to increase the alumina content in glass ingredients and reduce the melting temperature in glass production. In addition, microcline has a low crystallization ability after melting, which can protect the ceramsite structure from being destroyed. At the same time, the feldspar glass generated in the melting can make the ceramsite dense and reduce the voids to improve the mechanical strength and dielectric properties. Calcite, barite and rock salt contain a large amount of pyroxene raw materials, which react at high temperatures to form pyroxene. Finally, as described above, the organic matter in the four raw materials is modulated and solidified to obtain the microporous material.
[0068] The present invention utilizes a material that can promote the formation of fine honeycomb micropores in the raw ball material at high temperature, which can not only destroy the chemical composition of the original material to achieve the requirement of reducing the concentration of pollutants. At the same time, because most of the heavy metals, precious metals and other impurities form new phases and solidify in them under the action of high temperature, they exist in the environment for a long time, which not only avoids harm to the ecological environment, but also more importantly, it can reduce production costs, save energy and reduce carbon emissions, and promote the sustainable development of enterprises. It provides a way to solve a series of problems such as large output of hazardous waste and incineration products on land, complex components, difficult treatment, and high cost.
[0069] The product prepared by the present invention has a fine honeycomb microporous structure, and has the characteristics of excellent impermeability, low water absorption, heat resistance, high porosity, high compressive strength, strong stability in containing pollutants, low metal leaching, and no pollution to the environment, and can be applied to fields such as construction substrate use.
[0070] Example 1
[0071] A certain amount of four kinds of raw materials, namely oily sludge, rock chip cake, slag and fly ash, are selected, and the raw materials with large particle size are screened out through a sieve with a mesh particle size of 20 mm for crushing and stored in separate bags;
[0072] Take a certain amount of three kinds of small particle raw materials and fly ash after screening, and dry them in an oven at a drying temperature of 80°C. The moisture content of the four kinds of raw materials after drying is 1% respectively. Use a ball mill to pre-treat the raw materials. The processing time is controlled within 5 minutes to obtain a powder sample with a particle size of 300 meshes.
[0073] According to the mass percentage, the four powder samples were blended. The total mass of the four samples was 100 g, of which 30.4 g of oily sludge, 15.2 g of rock mud cake, 5.9 g of slag, and 48.5 g of fly ash were taken respectively, and 15 mL of water was added and kneaded into balls;
[0074] The obtained raw material balls were dried in an oven at a drying temperature of 100°C for 8 hours, cooled, taken out and sieved through a standard sieve with a pore size of 0.5 mm.
[0075] The screened balls were placed in a set-up muffle furnace for burning, and the preheating temperature was set to 500°C and the reaction time was 30 minutes. Then the muffle furnace roasting temperature and roasting time were set, where the temperature was controlled at 1100°C and the time was controlled at 75 minutes. The microporous material F1 prepared by landed hazardous waste and incineration products was obtained.
[0076] Example 2
[0077] The modulation process of Example 1 was repeated, with the only difference being that the blending mass of the four samples was changed, as follows: 16.1 g of oily sludge, 37.2 g of rock chip cake, 11.4 g of slag, and 35.3 g of fly ash were taken respectively, and 15 mL of water was added, and the mixture was kneaded into balls to obtain the microporous material F2 modulated with the landed hazardous waste and incineration products.
[0078] Example 3
[0079] The modulation process of Example 1 was repeated, with the only difference being that the sample blending mass was changed, specifically as follows: 3.0 g of oily sludge, 66.2 g of rock chip cake, 17.7 g of slag, and 13.1 g of fly ash were taken respectively, and 15 mL of water was added, and the mixture was kneaded into balls to obtain the microporous material F3 modulated with the landed hazardous waste and incineration products.
[0080] Comparative Example 1
[0081] The preparation process of Example 1 was repeated, with the only difference being that 3.0 g of oily sludge, 66.2 g of rock chip cake, 17.7 g of slag, and 13.1 g of fly ash were selected, 15 mL of water was added, the sample was kneaded into a ball, and the high-temperature roasting temperature was controlled at 1150°C for 75 min to obtain the microporous material F4 prepared from the landed hazardous waste and incineration products.
[0082] Structure and performance characterization
[0083] (1) Scanning electron microscopy was used to observe the microstructure of the microporous materials conditioned by the landed hazardous waste and incineration products. The results are shown in Figure 2 .
[0084] It was observed under a scanning electron microscope that the increase in the amount of rock cake and slag added and the decrease in the amount of oily sludge and fly ash added had a greater impact on the surface morphology of the microporous material. At the beginning, the structure was relatively loose, the surface was relatively rough, and it was uneven with many wrinkles, and the pores were difficult to find. As the amount of addition changed, the surface of the micropores became smoother and the number of pores increased significantly.
[0085] (2) TG-DSC analysis of raw material balls was performed using a thermogravimetric analyzer. The results are shown in Figure 3 .
[0086] observe Figure 3 It was found that the microporous material will undergo two stages of heating during the modulation process, namely heating and calcination, during which there will be four weight loss stages. The first weight loss stage is 90℃-200℃, and the capillary bound water and adsorbed water on the surface of the microporous material are evaporated. In addition, the increase in temperature is conducive to the decomposition of organic matter and promotes the occurrence of exothermic reactions. The second weight loss stage is 250℃-800℃, because the organic matter begins to volatilize and decompose, which promotes the generation and formation of gas and pores, avoiding the occurrence of cracking due to drastic changes in temperature. The third weight loss stage is 830℃-1040℃, the mineral composition changes, and the crystal structure is formed. The fourth weight loss stage is 1050℃-1170℃, and the weight loss phenomenon in this stage is the most obvious, with an exothermic peak at around 1150℃. During the sintering process of this stage, a series of redox reactions occurred, producing new phases and gases.
[0087] (3) X-ray diffractometer was used to analyze the microporous material before and after modulation. The results are shown in Figure 4 .
[0088] observe Figure 4 It was found that during the heating and roasting process of the raw material balls, a series of physical and chemical reactions occurred inside. Figure 4 From the left column of graphs, we can see that it contains a large amount of quartz, with a small amount of microcline, calcite, halite, barite and gypsum; Figure 4As can be seen from the right column of figures, the calcined product contains a large amount of quartz, albite and pyroxene; by comparison, it is found that Na2O, Al2O3 and SiO2 contained in the raw material ball will melt under high temperature conditions, and Na2O, Al2O3 and SiO2 will rearrange and combine together to form the structure of albite crystals. A small amount of microcline was found before and after calcination. Due to the high Al2O3 content and low iron content, it not only has a low melting temperature but also a wide melting range. It can be used as a material to increase the Al2O3 content in the glass batch and reduce the melting temperature in glass production. In addition, microcline has a low crystallization ability after melting, which can protect the ceramsite structure from being destroyed. At the same time, the feldspar glass generated in the melt can make the ceramsite dense and reduce the voids to improve the mechanical strength and dielectric properties. Calcite, barite and rock salt contain a large amount of pyroxene raw materials, which react at high temperatures to form pyroxene. Combined with the above analysis, it can be concluded that the internal structure and external morphology of the material have been stably formed, and it may have the excellent properties of a microporous material. Further testing of indicators such as heavy metal leaching toxicity and organic matter content is needed to verify it.
[0089] Performance test experiment
[0090] (1) The structural properties (including cylinder pressure strength, bulk density and water absorption rate) of the microporous materials prepared from the landed hazardous waste and incineration products of Examples 1-3 and Comparative Example 1 were tested to check whether they met the prescribed standards. The test results are shown in Table 1.
[0091] Table 1 Microporous material structure and performance
[0092] Indicator name Cylinder compressive strength (MPa) <![CDATA[Bulk density (kg / m 3 )]]> Water absorption (%) F1 Sample 4.03 635 8.42 F2 sample 5.01 709 7.22 F3 sample 6.72 847 6.11 F4 sample 10.94 718 7.30
[0093] From Table 1, it can be analyzed that the cylinder pressure strength and bulk density increase with the increase of the amount of rock cuttings mud cake and slag added, from 4.03MPa and 635kg / m 3 Increased to 6.68MPa, 846kg / m 3 The reason is that dehydrated rock cuttings and dehydrated cement cakes contain a large amount of SiO2, and the internal structure becomes compact and dense due to the high temperature during the roasting process; the water absorption rate decreases with the increase of the amount of rock cuttings cake and slag added. In the F1 sample, the fusible components are relatively rich, which promotes the occurrence of melting reactions, resulting in the formation of abundant pores inside and the increase of water absorption rate. However, as the amount of rock cuttings cake and slag continues to increase, a large amount of molten liquid phase will be formed, and the pores will be continuously filled, further resulting in a decrease in water absorption rate. Based on the F3 sample, the F4 sample will induce the occurrence of multi-directional synergistic effects in the crystal structure, gas production reaction and molten liquid phase by changing the roasting temperature, further promoting the increase of cylinder pressure strength and water absorption rate.
[0094] (2) The obtained microporous material was tested by heavy metal leaching toxicity, organic matter content and other indicators. The test results are shown in Table 2.
[0095] Table 2 Characterization of leaching toxicity and organic solidification index of microporous materials
[0096]
[0097]
[0098] The microporous material modulated with the landed hazardous waste and incineration products obtained by the above-mentioned adjustment method has a large amount of pollutants solidified therein under high temperature conditions, resulting in a thorough reduction of the heavy metal content, salt content and organic matter in the leaching toxicity. The leaching toxicity of harmful ions is far lower than the national standard limit, meeting the requirements for use in the field of building substrates.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing microporous materials from landed hazardous waste and incineration products, characterized in that: The following steps are involved: Step S1, taking a certain amount of four raw materials, namely, oily sludge, rock chip cake, slag, and fly ash, screening out the raw materials with large particle sizes for crushing, and then storing the four raw materials separately; Step S2, using an oven to dry the four raw materials respectively; Step S3, using a ball mill to process the oily sludge, rock chip cake and slag respectively; Step S4, the treated sample is mixed with fly ash according to the mass percentage, and the mixing time and particle size need to be controlled; Step S5, adding water to the mixed sample, and then kneading it into raw material balls; Step S6, placing the obtained raw material balls in an oven for drying; Step S7, the dried raw balls are sieved through a standard sieve to obtain semi-finished raw balls; Step S8, preheating the raw balls obtained after screening; Step S9, calcining the spherical material after the preheat treatment at high temperature; Step S10, after the furnace temperature is lowered, the spherical material is taken out and sieved to obtain the final microporous material required.
2. The method for preparing microporous materials from landed hazardous waste and incineration products according to claim 1, characterized in that: The hazardous waste brought ashore is oily sludge and rock debris cake, the incineration products are slag and fly ash produced by the operation of the incinerator, and the raw materials used to prepare the microporous material come from one or more of them.
3. The method for preparing microporous materials from landed hazardous waste and incineration products according to claim 2, characterized in that: In step S1, the raw materials with large particle sizes are screened out through a sieve with a mesh particle size of 20 mm; the raw materials are processed by a crusher so that the particle size of the raw material blocks is ≤ 25 mm; In step S2, when the four raw materials are dried separately, the drying temperature is 60°C-110°C, and the moisture content of the four raw materials after drying is ≤2%.
4. The method for preparing microporous materials from landed hazardous waste and incineration products according to claim 2, characterized in that: In step S3, the raw material is pre-treated by a ball mill for 5 min to 30 min to obtain a powder sample, and the particle size of the powder sample is ≤320 mesh.
5. The method for preparing microporous materials from landed hazardous waste and incineration products according to claim 2, characterized in that: In step S4, after the four powdery samples are blended according to the mass percentage, the mass percentage of the oily sludge is 2%-35%, the mass percentage of the rock chip cake is 15%-75%, the mass percentage of the slag is 3%-20%, and the mass percentage of the fly ash is 5%-50%.
6. The method for preparing microporous materials from landed hazardous waste and incineration products according to claim 2, characterized in that: Step S5 includes mixing the four raw materials and weighing them, adding water according to the weight, and controlling the amount of water added each time according to 3%-15% of the total weight of the mixed sample, and then kneading the mixed raw materials into raw material balls.
7. The method for preparing microporous materials from landed hazardous waste and incineration products according to claim 2, characterized in that: In step S6, the drying temperature is 80°C-100°C, and the drying time is 8h-20h; in step S7, the aperture of the standard sieve used for screening the raw balls is 0.4mm-1.0mm.
8. The method for preparing microporous materials from landed hazardous waste and incineration products according to claim 2, characterized in that: In step S8, the preheating temperature is set to 200°C-500°C and the holding time is 5min-60min during the preheating treatment; in step S9, the control temperature of the high temperature roasting is 1000°C-1260°C and the control time is 30min-120min.
9. The microporous material prepared by the method according to any one of claims 1 to 8.
10. Use of the microporous material according to claim 9 in the field of building substrates.
